Control 4.0: Creating a vision for the future of industrial control rooms under Industry 4.0 : Effective and attractive workplaces through Industry 4.0 - Sundström, Erik (Luleå tekniska universitet, Människa och teknik, 2019)
Today’s industries are facing what some may call a new industrial revolution. Technological developments are heading towards more internet-based system solutions. This movement is often referred to as Industry 4.0 and is said to have the potential for more flexible, autonomous productions capable of managing themselves. With new technologies, however, there is also a demand for new competences and qualification requirements on the workforce. Furthermore, industries of today often have problems with recruiting new competent employees, especially younger people. Industries looking to implement Industry 4.0 would therefore have to manage the education and development of existing employees while also attracting new employees. As part of a larger research project at Luleå University of Technology, this thesis project aims to describe how the control rooms in Swedish metallurgic industries will be affected by Industry 4.0. Furthermore, the project aims to describe what changes that are desirable for achieving a sustainable, effective and equal industry. To better achieve this goal, the project was done in collaboration with the metallurgic industry SSAB, specifically the steel production in Luleå. Through visits, interviews and observations at the control rooms in SSAB’s steel production, the context of today’s control room work was detailed. This context was compared to and analyzed using reviewed literature regarding future technologies under Industry 4.0 along with my own speculations on future possibilities. The analyses consists of my reflections on what problems that existed, what could be improved and what worked well in the control rooms. Furthermore, my analyses included the positive and negative effects that the implementation of Industry 4.0 technologies could have on the control room work. The analyses were utilized as the basis for creating a vision of how control rooms can develop under Industry 4.0, and the changes that are desirable. The resulting vision compiled from my analyses consists of two ...